An Expressway Development Strategy for Vietnam - World Bank (Washington, DC, 2013)
Vietnam's rapid economic growth continues to create new demands for transport infrastructure and services. Bottlenecks to business activities caused by infrastructure constraints are already appearing in several areas. High rates of urbanization, rising traffic accidents, new capacity constraints, and a large increase in asset preservation requirements to meet the fast expansion of transport assets presents further challenges to the sector. To address these infrastructure bottlenecks, and to gradually remove the transport constraints on industry, Vietnam is embarking on an ambitious expressway development program. To date the transport sector has facilitated this growth principally through the rehabilitation and widening of existing arterial roads. The national road network has expanded to 17,000 km, the overall condition has improved with 66 percent of the network being in good and fair condition and 84 percent of the network is now paved. If traffic growth rates continue at their current rate these constraints could adversely impact future economic development. The successful development of an expressway system is a significant physical and financial commitment which will require a number of changes to laws, regulations, institutions and operations of the network.